Contextualization of Maslahah Jasser Auda’s Thought in Islamic Economy - Achmad Fageh (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
The Division of Maslahah can be deduced into five kinds, namely; (1) based on the purpose of the day/Time, (2) based on the level of necessity, (3) based on its coverage (range), (4) based on the presence or absence of changes and (5) based on the presence or absence of the Shariah in the assignment. Maslahah based on the purpose of his day divided into two levels, namely; Maslahah the world and the Hereafter." Maslahah the world is the obligation or rule of Shara ' related to the laws of Muamalah instead (social and economic interactions). While Maslahah Hereafter is the obligation or restriction of Shara' about the rules of Aqidah (Tauhid) and Worship. Yasser Auda divided the Maslahah on the aspect of the need into three categories: (a) Maslahah al-Dlaruriyyah (primary benefit), (b) Maslahah al-Hajiyyah (secondary benefit) and (c) Maslahah al-Tahsiniyyah (benefit Tertiary). The concept of Maqasid offered by Auda is identical with Maslahah and the view of the Ulama about Maslahah and all type. Jasser Auda defines maqāṣīd in four meanings, first, the wisdom behind a law. Second, a good end goal that the Law was trying to achieve. Third, the divine purpose group and the moral concept are the basis of Law. Fourth, maṣālih. In the maqāṣīd idea offered by Auda, values and humanitarian principles are the most important. Auda also tried to reconstruct the old maqāṣīd concept, which is protection and preservation in the direction of the maqāṣīd theory, which refers to development and rights. The implications of the application of maqāṣid al-sharī’ah. Using the maṣlaḥah instrument in the context of the Islamic economy in Indonesia are used to fulfil the needs of sharia policies in the economic sector which do not only revolve around Islamic banking matters.